A quale ruolo "adulto" formerà la scuola? Riflessioni a par- tire dalla strategia europea Rethinking Education - Elena Marescotti (Firenze University Press, 2014)
This paper focuses on the European Commission Communication Rethinking Education: Investing in skills for better socio-economic outcomes (November 2012). The comments concern the school educational tasks and, in particular, the young-adult "identity" required to face multiple challenges of current global crisis. In an educational perspective, it require a "re-thinking" of education, maintaining a meaning horizon dedicated to the promotion of a "genuine" quality of life, and an anthropological project that cannot be sacrificed in the name of the contingent political and economic pressures. In a lifelong education view, this article considers the relationship between education/adult education and the meaning of adult identity, to improve the human "desirable" ideals vs than what is too often presented as "necessary evil".